2010
DOI: 10.1111/j.1440-1681.2010.05424.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cinnamtannin B‐1 on cholecystokinin‐8‐evoked responses in mouse pancreatic acinar cells

Abstract: SUMMARY1. Cinnamtannin B-1 is a naturally occurring A-type proanthocyanidin that belongs to a class of polyphenols widely distributed throughout the plant kingdom and exhibiting anti-oxidant properties.2. In the present study, we examined the effects of cinnamtannin B-1 on cholecystokinin octapeptide (CCK-8)-evoked Ca Cholecystokinin-8 had a biphasic effect on amylase secretion, producing maximum at a concentration of 0.1 nmol ⁄ L and reducing secretion at higher concentrations. Pre-incubation of cells with 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…By contrast, cpd5 was toxic to INS-1 cells, whereas cpd1 and cpd2 had no protective effect on pancreatic β-cells. The trimer procyanidins, cinnamtannin B1 and D1, inhibit cyclooxygenase-2 [23] , whereas cinnamtannin B1 exerts anti-oxidative effects in pancreatic acinar cells [24] . Our recent study also showed that cinnamtannin D1 protects against PA-induced β-cell dysfunction by attenuating oxidative stress and reducing nuclear factor kappa B (NF-κB) activation [16] .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, cpd5 was toxic to INS-1 cells, whereas cpd1 and cpd2 had no protective effect on pancreatic β-cells. The trimer procyanidins, cinnamtannin B1 and D1, inhibit cyclooxygenase-2 [23] , whereas cinnamtannin B1 exerts anti-oxidative effects in pancreatic acinar cells [24] . Our recent study also showed that cinnamtannin D1 protects against PA-induced β-cell dysfunction by attenuating oxidative stress and reducing nuclear factor kappa B (NF-κB) activation [16] .…”
Section: Discussionmentioning
confidence: 99%
“…17 As reported, the main components of extracts were A-type procyanidin trioligomers, including >43% CD1 and >23% CB1, one structural isomer of CD1. 17 A-type polymers were reported to reduce peroxide-induced pancreatic acinar cell injury, 27,28 generate insulin-like biological activity, 13 and improve insulin sensitivity in vivo. 29 However, as effective antioxidants 24 and the major components of antidiabetic natural products, 17 the effects of A-type polymers in C. tamala have not yet been explored on insulin-secreting β-cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This could represent a pathogenetic mechanism of autodigestion of the gland that might lead to the onset of pancreatic inflammation [68]. The underlying cause responsible for the impairment of enzyme secretion could involve intracellular Ca 2+ accumulation and concomitant oxidative stress [69][70][71]. The relationship between AA and Ca 2+ signaling has been studied (see above).…”
Section: Role Of Arachidonic Acid In Pancreatitis and Diabetesmentioning
confidence: 99%